Analysis of luciferase dsRNA production during baculovirus infection of Hi5 cells: RNA hairpins expressed by very late promoters do not trigger gene silencing - Kolliopoulou, Anna; Kontogiannatos, Dimitrios; Mazurek, Aleksander Józef; Prifti, Izabela; Christopoulou, Vasiliki-Maria; Labropoulou, Vassiliki; Swevers, Luc (Frontiers in Insect Science, 2022)
The baculovirus expression vector system (BEVS) has become an important platform for the expression of recombinant proteins and is especially useful for the production of large protein complexes such as virus-like particles (VLPs). An important application for VLPs is their use as vehicles for targeted delivery of drugs or toxins which requires the development of methods for efficient loading with the intended cargo. Our research intends to employ the BEVS for the production of VLPs for the delivery of insecticidal dsRNA molecules to targeted insect pests (as “dsRNA-VLPs”). A convenient strategy would be the co-expression of long dsRNAs with viral capsid proteins and their simultaneous encapsulation during VLP assembly but the capacity of the BEVS for the production of long dsRNA has not been assessed so far. In this study, the efficiency of production of long RNA hairpins targeting the luciferase gene (“dsLuc”) by the polyhedrin promoter during baculovirus infection was evaluated. However, RNAi reporter assays could not detect significant amounts of dsLuc in Hi5 cells infected with recombinant baculovirus, even in the presence of co-expressed dsRNA-binding protein B2-GFP or the employment of the MS2-MCP system. Nevertheless, dot blot analyses using anti-dsRNA antibody revealed that baculovirus-mediated expression of B2-GFP resulted in significant increases in dsRNA levels in infected cells that may correspond to hybridized complementary viral transcripts. Using B2-GFP as a genetically encoded sensor, dsRNA foci were detected in the nuclei that partially co-localized with DAPI staining, consistent with their localization at the virogenic stroma. Co-localization experiments with the baculovirus proteins vp39, Ac93, ODV-E25 and gp64 indicated limited overlap between B2-GFP and the ring zone compartment where assembly of nucleocapsids and virions occurs. Stability experiments showed that exogenous dsRNA is resistant to degradation in extracts of non-infected and infected Hi5 cells and it is proposed that strong unwinding activity at the virogenic stroma in the infected nuclei may neutralize the annealing of complementary RNA strands and block the production of long dsRNAs. Because the strong stability of exogenous dsRNA, transfection can be explored as an alternative method for delivery of cargo for dsRNA-VLPs during their assembly in baculovirus-infected Hi5 cells.